Management Analysis of Village-Owned Enterprises (Bumdes) in Sharia Business Management (Case Study at BUMDes Mandiri Jaya Pemusiran Village, Mandiangin District) - Sari Asih; Rafiqi .; Ary Dean Amri (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2023)
BUMDes is a village-owned business institution controlled by the community or village government to strengthen the village economy and shape the capabilities of a village based on the needs and potential of the community and village. The establishment of BUMDes is a manifestation of productive village economic management which includes planning, organizing, directing and supervision. This research aims to determine the management of BUMDes in Sharia business management. The research method used in this research is qualitative research with a descriptive approach. Data sources obtained through observation and interviews. The results of this research show that BUMDes Mandiri Jaya, Pemusiran Village, Mandiangin District, which started operating in 2017 in Pemusiran Village, has been running in accordance with the objectives of establishing BUMDes. However, there are still obstacles in managing BUMDes, such as limited types of businesses being run, limited human resources managing BUMDes and low community participation due to their low level of knowledge.